Examining the logical argument of the problem of evil from an African perspective - Chimakonam, Jonathan O. (Religious studies, 2023)
We argue that the problem of evil, logically, stems from the unequal binary that characterizes the bivalent structure of Western discourses in the philosophy of religion. This structure pits God against the devil, but also the value of good against evil they are believed to represent. The difficulty is that those who subscribe to creationism, for example, hold that God as an omniscient, omnipotent, and morally perfect entity created everything. Ironically, this must include evil or the devil himself. If one says He did not create evil, then one is faced with the challenge of explaining how evil emerged and how an omniscient, omnipotent, and morally perfect God could continue to allow evil in the world. Our strategy would be to dilute the problem by dismantling logical bivalence. With an appropriate logic background like the African truth-glut three-valued system of Ezumezu as an explanatory mechanism, we will demonstrate that the problem of evil is resolvable, even if negatively. Using the principle of value-complementarity, we will argue that the notions of good and evil are not merely opposites but complementary. In this way, God, would be construed, especially from logical ideas inspired by the viewpoint of the African Traditional world-view, as ‘harmony-God’.